Dry sandpits and gravel–sandpits serve as key refuges for endangered epigeic spiders (Araneae) and harvestmen (Opiliones) of Central European steppes aeolian sands - Heneberg, Petr; Řezáč, Milan (Ecological engineering, 2014)
[Display omitted] •Czech xerothermophilous sandpit habitats host 323.8±23.9 spider species.•Czech xerothermophilous sandpit habitats host 8.5±1.1 harvestmen species.•6 CR, 17 EN, 29 VU and 29 NT species were detected at sandpit xerothermes.•72 (89%) of rare species were present at spontaneously formed sandpit xerothermes.•Sandpit (post) industrial habitats host highly diverse spider communities. Although the value of the habitat lost by quarrying is widely known, awareness of the conservation value of the newly formed habitat is negligible. We provide evidence on the conservation value of both active and disused sandpits and gravel–sandpits for epigeic spiders and harvestmen, commonly considered important indicator species. We focus on xerothermophilous habitats within sandpits subjected to near-natural succession or other reclamation efforts. We show that xerothermophilous sandpit microhabitats are used by 323.8±23.9 epigeic spider species and 8.5±1.1 harvestmen species, with the species spectrum changing dramatically during spontaneous succession and if the habitat is subject to other forms of reclamation, with low species dominance across all habitats tested. We found 81 spider species recognized as critically endangered, endangered, vulnerable or nearly threatened. Of these, 72 (89%) were present at spontaneously formed xerothermophilous habitats of various ages, and 40 (49%) at the reclaimed sites. We analyzed the species-specific habitat preferences of the red-listed spider species in relation to both abiotic (altitude, slope, soil penetration resistance, soil shear strength resistance, soil texture) and biotic (vegetation cover, plant diversity, diversity of red-listed plants) factors. The xerothermophilous sandpit habitats served as important refuges for Central European steppe and aeolian sand dune species, which had nearly disappeared from the surrounding intensively cultivated cultural landscape.